2020
DOI: 10.21203/rs.3.rs-61979/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection of metastasis competent subclones in the tumour interior: TRACERx renal

Abstract: While the genetic evolutionary features of solid tumour growth are becoming increasingly described, the spatial and physical nature of subclonal growth remains unclear. Here we utilise 102 macroscopic whole tumour images from clear cell renal cell carcinoma (ccRCC) patients, with matched genetic and phenotypic data from 756 biopsies. Utilising a digital image processing pipeline the boundaries between tumour and normal tissue were marked by a renal pathologist, and positions of boundary line and biopsy regions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…We hypothesize that in PDOs with these expression signatures, the cells that exhibit a MYC-low/hypoxia-high profile are the likely candidates for chemotherapy escape (Fig 7F). Additionally, fate mapping and other studies have shown that tumor cells exposed to hypoxia have a higher tendency to result in metastasis (62, 63). It remains to be tested to what extent these MYC-low/hypoxia-high cells contribute towards metastasis and/or chemotherapy resistance, and these patient-derived organoids will be an invaluable tool to answer these questions.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesize that in PDOs with these expression signatures, the cells that exhibit a MYC-low/hypoxia-high profile are the likely candidates for chemotherapy escape (Fig 7F). Additionally, fate mapping and other studies have shown that tumor cells exposed to hypoxia have a higher tendency to result in metastasis (62, 63). It remains to be tested to what extent these MYC-low/hypoxia-high cells contribute towards metastasis and/or chemotherapy resistance, and these patient-derived organoids will be an invaluable tool to answer these questions.…”
Section: Discussionmentioning
confidence: 96%
“…Evolution is the driving force behind cancer cell resistance or metastasis 122,123 . Previous research largely relied on multi‐region sample collection, 124 where directly modelling the spatial evolutionary routes cell‐by‐cell was far from applicable. Now, with the help of spatial omics, tracing cancer evolution at different space coordinates and cellular units is now possible.…”
Section: Spatial Omics In Cancer Research: From Bench To Bedsidementioning
confidence: 99%
“…[131] The core of the tumorous mass is the true intended target for targeted cancer therapy as this is where the most aggressive sub-clonal growth stems from resulting in increased proliferation, somatic copy number, and Fuhrman grade. [132] To reach the core, additional strategies may be employed to facilitate movement into this region including the functionalization of CDs with "enhanced permeability and retention" agents or triggering CDs with external radiation stimuli (i.e., ultrasound, radiotherapy, photodynamic, or hyperthermia) to physically enhance access (Figure 4). [24]…”
Section: Tumor Microenvironmentmentioning
confidence: 99%